"Lo que el pueblo necesita". Turismo social y Peronismo. Argentina, 1945-1955 - Elisa Pastoriza; Marcelo Pedetta (Études Caribéennes)
Throughout J.D. Peron’s first two terms in office (1946-1955), against the backdrop the so-called “welfare democratization” process, leisure and free time progressively gained momentum. Vacation habits in the middle and working classes became richer thanks to both public policies and civil initiatives. During this period, the National State not only re-adopted previous programs, but it also opened new channels favoring the entrance of the abovementioned sectors into the recreational-activity market. The purpose of this presentation is to analyze some of these policies, highlighting their reception by, and impact on, the middle and working classes. To this end, a methodological exercise will be carried out on the basis of a privileged source: the archives of the “Secretaría Técnica. Primera y Segunda Presidencia del General Juan Domingo Perón (1946 – 1955)”, a collection of documents summarizing the answer –by way of letters– of the populace to the State’s call during the elaboration of the second five-year plan.